Geometry calibration between X-ray source and detector for tomosynthesis with a portable X-ray system - Sato, Kohei (Int J Comput Assist Radiol Surg, 2017)
PURPOSE: Tomosynthesis is attracting attention as a low-dose tomography technology compared with X-ray CT. However, conventional tomosynthesis imaging devices are large and stationary. Furthermore, there is a limitation in the working range of the X-ray source during image acquisition. We have previously proposed the use of a portable X-ray device for tomosynthesis that can be used for ward rounds and emergency medicine. The weight of this device can be reduced by using a flat panel detector (FPD), and flexibility is realized by the free placement of the X-ray source and FPD. Tomosynthesis using a portable X-ray device requires calibration of the geometry between the X-ray source and detector at each image acquisition. We propose a method for geometry calibration and demonstrate tomosynthesis image reconstruction by this method. METHODS: An image processing-based calibration method using an asymmetric and multilayered calibration object (AMCO) is presented. Since the AMCO is always attached to the X-ray source housing for geometry calibration, the additional setting of a calibration object or marker around or on the patients is not required. The AMCO’s multilayer structure improves the calibration accuracy, especially in the out-of-plane direction. RESULTS: Two experiments were conducted. The first was performed to evaluate the calibration accuracy using an XY positioning stage and a gonio stage. As a result, an accuracy of approximately 1 mm was achieved both in the in-plane and out-of-plane directions. An angular accuracy of approximately [Formula: see text] was confirmed. The second experiment was conducted to evaluate the reconstructed image using a foot model phantom. Only the sagittal plane could be clearly observed with the proposed method. CONCLUSION: We proposed a tomosynthesis imaging system using a portable X-ray device. From the experimental results, the proposed method could provide sufficient calibration accuracy and a clear sagittal plane of the reconstructed tomosynthesis image.